Effects of natural convection on latent heat storage performance of salt in a horizontal concentric tube. (1st April 2015) - Tao, Y.B.; He, Y.L.
Highlights: Effects of PCM natural convection on LHS performance were investigated. Natural convection causes nonuniformity of LHS process. Local enhanced fin-tube was designed to improve the uniformity. Effects of fin parameters were examined. Optimum fin parameters were recommended. Abstract: Three-dimensional numerical studies were performed for latent heat storage (LHS) process of salt in a horizontal concentric tube to investigate the effects of liquid phase change material (PCM) natural convection on LHS performance. The results show that due to the effects of natural convection, the high temperature molten salt flows upward which enhances the PCM melting rate in upside and weakens the melting rate in downside. So, although the natural convection can enhance the heat transfer performance of liquid PCM, it also causes larger non-uniformity for the solid–liquid interface and temperature distribution during the PCM melting process. Then a local enhanced fin-tube was designed to improve the uniformity of the melting process. The effects of fin geometric parameters on the LHS performance were numerically investigated. The results show that the local fins can improve the uniformity of the LHS process. However, the fin parameters should be appropriately selected because the excessive large fin parameters will break the uniformity again. In present paper, the following fin parameters are recommended: fin number, 7; dimensionless fin thickness, 0.1; dimensionless fin height, 0.8.